A Review on Role of Pushpadhanwa Rasa in Ovulation Induction for Management of Anovulatory Factor of Infertility. - Irfan, Sana; Saxena, Anjana; Srivastava, Sarika (International Research Journal of Ayurveda & Yoga, 2023)
The integral part of achieving Sreyasi Praja are Garbhasambhava Samagri which includes Ritu (fertile period), Kshetra (uterus and reproductive organs), Ambu (proper nutrient fluid) and Beeja (Shukra Shonita) and also normalcy of Hrdaya (psychology). As there are many causes for Vandyatwa mentioned, in this study Vandyatwa due to Arthava Nasha or Ovulation disorders account for about 30-40% of female infertility. Anovulation is the failure to produce a mature ovum by ovary. Anovulation is caused due to defect in the function of the hypothalamo-pituitary-ovarian axis. Aartava is considered as ovum and it is formed as a updhatu after proper digestion of ahara rasa by prakrit agni. If agni is disturbed by ahita aharavihara formation of rasadi dhatu and thereby formation of artava is also affected causing “Nashtartava” which can be considered as anovulation. In such patients ovulation induction is a rescuer. In Ayurveda, Vandhyatva is a Vata Dosha Pradhana Vyadhi and Ovulation is under the control of Vata especially Apana Vata. Vandhyatva due to ovarian factor is Vata-Kapha Pradhan Vyadhi. It is Vikruti of Vata Dosha i.e., Apana Vayu Karmatah Hani occurs. Hence main line of treatment could be Vata Kapha Shamaka, Agnidipana, Pachaka and Vatanulomaka and Brimhana which is the line of management to correct the Samprapti and to restore fertility.